109 Near-fatal suicide attempts among Canadian Youth: A CPSP Study. (19th August 2020) - Mitchell, Rachel; Ani, Cornelius; Irvine, James; Cyr, Claude; Joffe, Ari; Skinner, Robin; Stang, Antonia; Wong, Sam; Yao, Xiaoquan; Korczak, Daphne J
Abstract: Background: Suicide is the second leading cause of death among Canadian adolescents. Youth who make near fatal suicide attempts, such as those requiring intensive care unit (ICU) level care, are the closest proxy to those that die by suicide; however, there is limited data on this group. Objectives: To evaluate the minimum incidence rate and patterns of presentation of youth (under 18 years of age) admitted to the ICU for medically serious self-inflicted injury. Design/Methods: From January 2017 to December 2018, over 2, 700 paediatricians/subspecialist members of the Canadian Paediatric Surveillance Program were electronically surveyed on a monthly basis regarding cases of medically serious self-harm. Participants completed a detailed questionnaire about the reported case and descriptive statistics were used for analyses. Results: Ninety-four cases (71 female; mean age 15.2 years) of confirmed (n=87) and suspected/probable (n=7) medically serious self-harm were reported. The majority (87%) of cases were reported from 4 out of 13 provinces and territories in Canada (Alberta, British Columbia, Ontario, Quebec). There were 11 deaths by suicide (M>F; p <.05). Medication ingestion was the most common method of self-harm among females (76% F vs. 52% M; p =.03) compared with hanging among males (14% F vs. 39% M; p =.009). More females than males had a prior suicide attempt (62% F vs. 32% M; p =.07) and a history of non-suicidal self-injury (NSSI) (65% F vs. 14% M; p <.05), although only history of NSSI reached significance. More females than males had a past psychiatric diagnosis (77% F vs. 55% M; p =.05), and past use of mental health services (69% F vs. 30% M; p <.001), although only service use reached significance. Half of the youth left evidence of intent (54%) and 33% of parents of included youth were aware that their child was considering suicide. Family conflict was the most common precipitating factor for suicide attempt in both females and males (46%). Conclusion: These Canadian findings are consistent with international epidemiologic data that observe a gender paradox of higher rates of suicide attempts in females and greater mental health care engagement but increased suicide mortality in males with decreased involvement with mental health care. This study suggests that family conflict is a potential target for suicide prevention interventions among youth. Future research focusing on gender-specificity in risk factor identification and effectiveness of primary prevention interventions among youth is warranted.